Pottery production of Saujil vessels from the early period (Catamarca and La Rioja provinces), Northwestern Argentine region : an evaluation through neutron activation analysis - Ratto, Norma Rosa (2021)
Fil: Ratto, Norma Rosa. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Saavedra 15. Instituto de las Culturas. Universidad de Buenos Aires. Instituto de las Culturas; Argentina.